mpitb: a toolbox for multidimensional poverty indices - Suppa, N (SAGE Publications, 2023)
This paper presents mpitb a toolbox for multidimensional poverty indices (MPI). The Stata package mpitb comprises several subcommands to facilitate specification, estimation, and analyses of MPIs and supports the popular Alkire-Foster framework to multidimensional poverty measurement. mpitb offers several benefits to researchers, analysts and practitioners working on MPIs, including substantial time savings (e.g., due to lower data management and program- ming requirements) while allowing for a more comprehensive analysis at the same time. Besides various convenience functions mpitb also provides low-level tools for advanced users and programmers.